Artificial intelligence transforming the publishing industry: a case of the book sector in Africa - Salani, Justin; Tapfuma, Mass Masona (Frontiers in Research Metrics and Analytics, 2025)
The increasing availability and accessibility of artificial intelligence have triggered a seismic transformation of the publishing value chain, presenting unprecedented opportunities and challenges for publishers. Artificial Intelligence (AI) has been integrated into the entire publishing value chain, streamlining the processes of content acquisition by authors and publishers, content and product development, as well as the marketing and distribution of products. However, the disruptive force of AI renders some publishing functions obsolete and transforms the production and distribution of materials, and subsequently, knowledge dissemination. Despite the acknowledged value and potential of integrating especially generative artificial intelligence in the publishing industry, concerns have been raised over integrity, copyright and intellectual property rights in AI-generated content, text and data mining. The impetus of this study emanates from a dearth of literature on the adoption, challenges and opportunities associated with the integration of AI in the production, dissemination and distribution of publications in the book sector in Africa. This paper explores the role of artificial intelligence in the production and distribution of teaching and learning materials by educational publishers. Informed by the disruptive innovation theory, this conceptual paper provides a review of the extant literature on the integration of artificial intelligence in the educational publishing value chain in Africa and its implications on creativity, integrity and intellectual property rights issues associated with AI-generated content. The paper will proffer recommendations.